2016
DOI: 10.14238/pi45.4.2005.177-81
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of factor VIII inhibitor in patients with severe hemophilia-A and its clinical characteristics

Abstract: Background Hemophilia is a hereditary blood-clotting disorderdue to factor VIII deficiency. Up to this date, the administration offactor VIII in preventing and managing bleeding has been the maintreatment. One of the complications, which may occur due to re-peated administrations of factor VIII, is the formation of factor VIIIantibody (factor VIII inhibitor).Objective To find out the prevalence of severe hemophilia-A withfactor VIII inhibitor and its clinical characteristics.Methods A cross-sectional descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Haemophilia is an impairment of the blood-clotting process that results in repeated spontaneous bleeding in joints and muscles [ 22 ]. In Indonesia, haemophiliacs are treated only if bleeding occurs [ 23 ]. We included patients with severe/moderate levels who usually had 1 bleeding/month [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…Haemophilia is an impairment of the blood-clotting process that results in repeated spontaneous bleeding in joints and muscles [ 22 ]. In Indonesia, haemophiliacs are treated only if bleeding occurs [ 23 ]. We included patients with severe/moderate levels who usually had 1 bleeding/month [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In this study, another frequent bleeding location that was a combination of hemarthrosis-and hematomas-developed inhibitor. A previous study stated that hemarthrosis is a typical bleeding manifestation found in severe hemophilia, especially in patients receiving no maintenance treatment or prophylactic FVIII treatment [25]. Other previous studies also demonstrated that there was an insignificant correlation between bleeding type or location and inhibitor development [5,25].…”
Section: Discussionmentioning
confidence: 96%
“…In severe hemophilia A, recurrent clinical and subclinical joint bleeding episodes might occur all the time, gradually leading to irreversible changes such as hemophilic arthropathy (HA) [1,25]. In spite of numerous studies, the pathophysiology of HA has not been fully elucidated, especially as regards immunopathological mechanisms which are associated with the subclinical and early stage of the disease and to be more precise, with chronic joint inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of factor VIII inhibitors in hemophilia patients varies greatly, but overall ranges are from 3.6% to 52%. The prevalences of inhibitors in Taiwan, Jordan, and Saudi Arabia are 10.4%, 9%, 9.7%, respectively, whereas the prevalences in 1,[6][7][8] Indonesia vary from 35% to 37.5%. Inhibitors are problem in management of hemophilia because 2 treatment becomes difficult and expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Hemophilia is a bleeding disorder due to hereditary coagulation abnormalities, inherited by [1][2][3] X-linked recessive.…”
Section: Introductionmentioning
confidence: 99%